“Determinación de los niveles de contaminación a la atmósfera por emisiones de CO en el Distrito Metropolitano de Quito” - Burgos Tatés, Juan Diego (2023)
An investigation was carried out with the purpose of analyzing the air quality in the Metropolitan District of Quito and comparing with the current regulations in force based on the information collected by the monitoring stations of the Quito Environment Secretary for the years 2018, 2019, 2020 and 2021, where the descriptive quantitative research design was applied, with the review of the bibliography, data systematization and subsequent statistical analysis, the Quiteño Air Quality Index was used as a reference. to determine the condition of contamination and the possible affectation to health.